VALUASI SAHAM EMITEN AALI DAN SMAR DENGAN METODE DCF, CFROI, DAN RV PERIODE 2017-2027 - Chandra, Luciana; Lumbantobing, Rudolf; DR. Tampubolon, Lambok (GEMA EKONOMI, 2023)
This research is a descriptive case study with quantitative method. The research object in this case study is PT Astra Agro Lestari Tbk and PT SMART Tbk, two plantation sub sector company that listed on Indonesia stock exchange period February 2022 until February 2023. This research is to calculate the intrinsic value of PT Astra Agro Lestari Tbk (AALI) and PT SMART Tbk (SMAR) from fundamental view. The intrinsic value is obtained from stock valuation calculation, which is started by top-down analysis. Top-down analysis covers the analysis of Indonesia’s macro economic condition, government’s policies, palm-oil industry analysis, and the firm’s competitive advantage. The results from top-down analysis are used as the base to do stock valuation using Discounted Cash Flow method, Cash Flow Return on Investment method, and Discounted Dividend Model method. In Discounted Cash Flow method, the free cash flows used are Free Cash Flow to Firm and Free Cash Flow to Equity. From the stock valuation result, the intrinsic value of PT Astra Agro Lestari Tbk using: (1) Free Cash Flow to Firm model, the intrinsic value is Rp 34.092 per share; (2) Free Cash Flow to Equity model, the intrinsic value is Rp 35.176 per share. At the same time, for the Net Cash Flow Return on Investment method, PT Astra Agro Lestari Tbk recorded 25,92%. Then, the intrinsic value of PT Astra Agro Lestari Tbk using: (1) Free Cash Flow to Firm model, the intrinsic value is Rp 18.763 per share; (2) Free Cash Flow to Equity model, the intrinsic value is Rp 2.479 per share. At the same time, for the Net Cash Flow Return on Investment method, PT SMART Tbk recorded 5,26%. For the results of intrinsic value and also the ratios in Relative Valuation, PT Astra Agro Lestari Tbk and PT SMART Tbk have the potential to increase their stock price following their fair value. So that investors can place buy positions.